Rapid Detection of Tomato Spotted Wilt Virus With Cas13a in Tomato and Frankliniella occidentalis - Zhang, Wanhong; Jiao, Yubing; Ding, Chengying; Shen, Lili; Li, Ying; Yu, Yanbi; Huang, Kun; Li, Bin; Wang, Fenglong; Yang, Jinguang (Frontiers in Microbiology, 2021)
As one of the top 10 plant viruses, the severity of losses to crop productivity caused by Tomato Spotted Wilt Virus (TSWV) has resulted in an urgent need to develop a more sensitive and rapid detection method. In this study, we developed a CRISPR/Cas13a-based detection system to diagnose TSWV in tomato and the western flower thrips (Frankliniella occidentalis). The detection system relies on recombinase polymerase amplification (RPA) and Cas13a-mediated collateral cleavage activity. Positive results can be distinguished by a significantly enhanced fluorescence signal after 20 min. We tested the sensitivity of CRISPR/Cas13a-based detection system. We found that the detection system that we developed has limits of detection that reach 2.26×102 copies/μL and a 10-fold increase compared with the sensitivity of using RT-PCR to detect the virus. Furthermore, the CRISPR/Cas13a-based detection system has a high selectivity for TSWV without interference from other viruses. The CRISPR/Cas13a-based detection system was utilized to detect TSWV in samples of tomato leaves and the transmission vector F. occidentalis that were in complete agreement with the results using RT-PCR to detect the virus.